INTEGRATED APPROACHES TO LEGAL SUPPORT FOR THE INCLUSIVENESS OF PUBLIC TRANSPORT IN UKRAINE - Polishchuk, Inna; Senko, Alina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to study and analyse the need for and the importance of applying integrated approaches in the legal framework for inclusiveness of public transport at the current stage of development of Ukraine. Research methods: to achieve this goal, general scientific and special research methods were used: cognition, formal logic, comparison, generalisation, as well as methods of systematic analysis and synthesis of scientific sources and regulatory frameworks that define the issues raised by the work. Results: based on the analysis of the regulatory framework and scientific literature, the article identifies and specifies the existing problems of the current state of legal regulation of ensuring equal access of all citizens to transport services, especially persons with disabilities and other low-mobility groups, in the context of implementation of inclusiveness and barrier-free environment in the field of public transport. It is substantiated that in order to solve the problem of inclusiveness in the field of public transport, it is necessary to take into account the integration of all approaches, including modernisation of strategic planning, updating the design of the State’s social policy, public involvement, improvement of the regulatory framework, implementation of international standards and models of providing accessible transport services for these categories of population. At the same time, the existing set of threats and challenges for Ukrainian society requires new approaches and strategies to implement legal support for the development of inclusive public transport. Discussion: determining the priority of integrated approaches in the legal support of public transport inclusiveness in the context of implementing the state’s social policy through the use of various instruments of influence and implementation of targeted programmes, adaptation of new strategies and changes in legislation, which should take into account the real state of affairs in the country and positive practices of international experience in creating an inclusive environment. The need for further scientific research into the legal regulation of public transport inclusiveness, which should be based on the globalised doctrine of regulating the problems of ensuring equal opportunities and access to transport services for all citizens.